Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acsami.7b08407
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photocatalyst Based on a CdS Quantum Dots/ZnO Nanosheets 0D/2D Heterojunction for Hydrogen Evolution from Water Splitting

Abstract: A novel CdS/ZnO heterojunction constructed of zero-dimensional (0D) CdS quantum dots (QDs) and two-dimensional (2D) ZnO nanosheets (NSs) was rationally designed for the first time. The 2D ZnO NSs were assembled into ZnO microflowers (MFs) via an ultrasonic-assisted hydrothermal procedure (100 °C, 12 h) in the presence of a NaOH solution (0.06 M), and CdS QDs were deposited on both sides of every ZnO NS in situ by using the successive ionic-layer absorption and reaction method. It was found that the ultrasonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(108 citation statements)
references
References 60 publications
3
103
0
Order By: Relevance
“…For photoinduced water splitting, semiconductors such as TiO 2 , ZnO have been studied extensively . But corrosion of these catalysts, recombination of charges, and the wide band gap of such materials decreases their stability.…”
Section: Application Of Mncs In Energy Conversionmentioning
confidence: 92%
See 1 more Smart Citation
“…For photoinduced water splitting, semiconductors such as TiO 2 , ZnO have been studied extensively . But corrosion of these catalysts, recombination of charges, and the wide band gap of such materials decreases their stability.…”
Section: Application Of Mncs In Energy Conversionmentioning
confidence: 92%
“…For photoinduced water splitting, semiconductors such as TiO 2 , ZnO have been studied extensively. [201,202] But corrosion of these catalysts, recombination of charges, and the wide band gap of such materials decreases their stability.T oo vercome these problems, mostly NPs of noble metals (Au, Ag, and Pd) have been used. [203][204][205] In addition, the efficiency of these catalysts can be improved by using small-and monodisperse metal NPs as aco-catalyst to increasethe lifetimeofseparated charges and achieve good compatibility with the band gap of the semiconductors.…”
Section: Mncs As Co-catalyst In Photocatalysisfor Water Splittingmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38] In such geometry, semiconductors with large specific surface area and high conductivity usually serve as host skeletons, while the narrow band gap semiconductors with high visible light absorption coefficient coat on the host skeleton surface as guest materials. [31][32][33][34][35][36][37][38] In such geometry, semiconductors with large specific surface area and high conductivity usually serve as host skeletons, while the narrow band gap semiconductors with high visible light absorption coefficient coat on the host skeleton surface as guest materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, single‐phase CdS QDs are not photostable and photocorrosion may take place during photocatalysis. Diverse approaches implemented to overcome these issues include forming a heterostructure of CdS QDs with other semiconductors, polymers, and/or surface loading of noble‐metal cocatalysts . Kandi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover,s ingle-phase CdS QDs are not photostable and photocorrosion may take place during photocatalysis. Diverse approaches implemented to overcome these issues include formingaheterostructure of CdS QDs with other semiconductors, [8][9][10] polymers, [11] and/or surfacel oading of noble-metalc ocatalysts. [12][13][14] Kandi et al reported the synthesis of CdS QD/BiOI composites to study their photocatalytic activities for rhodamine Bd egradation and hydrogen production under solar-and visible-light irradiation, respectively.…”
Section: Introductionmentioning
confidence: 99%